ANALYSIS OF STUDENTS MISCONCEPTION IN CHEMICAL EQUILIBRIUM MATERIAL USING THREE TIER TEST - Khairunnisa Khairunnisa; AK. Prodjosantoso (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to analyze students misconception seen from the relationship between the results of the three tier test and interviews about chemical equilibrium material on the concept of determining the formula Kc, Kp, and the concept of Kc calculation. The research method was descriptive qualitative method. The data collection technique in this study was a test. The research instrument was in the form of three tier test questions consisted of four concepts. The misconceptions were analyzed based on the result of tests given to 30 students were further clarified by interviewing as matching answers. The study was conducted at SMA Negeri 2 Wonosari in Gunungkidul Regency with five interviewed research subjects. The result showed that students experienced misconceptions about the concept of determining the Kc formula by 23.33%, determining the Kp formula by 13,33%, and concept of Kc calculation by 16,67%.